Faktor Determinan Status Gizi Berdasarkan Indeks Masa Tubuh menurut Umur pada Anak Migran - Shofia Asri Nur'aini; nurhayati nurhayati; Nike Arta Puspitasari (Universitas Faletehan, 2026)
Nutritional status is a key indicator reflecting children’s health and growth. Migrant children are at higher nutritional risk due to limited access to healthcare services, inadequate living environments, and suboptimal dietary patterns. This study aimed to analyze the determinants of nutritional status based on Body Mass Index-for-Age (BMI-for-Age) among migrant children aged 6–12 years. This study employed an analytical quantitative design with cross-sectional approach. A total of 33 respondents were selected using purposive sampling. Data were collected through an online questionnaire completed by parents/guardians and direct anthropometric and hemoglobin examinations. Data analysis included Chi-square and logistic regression tests. The results showed that most children were classified as underweight/thinness (69.7%). Iron tablet consumption (OR=2.80) and water source type (OR=2.50) showed a tendency to be associated with nutritional status. The study recommends strengthening school-based health education, improving access to clean water, routine growth monitoring, and encouraging regular iron supplementation as promotive-preventive strategies among migrant children. These findings are expected to contribute to the development of nutrition and health interventions for vulnerable migrant children and to enrich the literature on child health disparities.